Genus Crotalaria L. (Leguminoseae) - Silva-López, R. E. S. (2013)
Legumes of the genus Crotalaria are native to India, with broad adaptation to tropical regions of the world. The name of Crotalaria refers to the rattle of dry pods, similar to the rattlesnake (Crotalus sp.). They are shrubs growing upright and determined, and its main job is the green manure. Furthermore, they can also be used as trap plants in soils infested with nematodes in endemic regions of Dengue in nitrogen fixation in crop rotation systems, industry and paper fibers and phytoremediation. Despite the high toxicity of its seeds due to presence of monocrotaline, protease inhibitors and other compounds, many molecules have been isolated and purified and its potential application has been studied. Extracts of some Crotalaria species were tested against bacteria, insects and parasites and the results were very promising. This paper aims to compile these results and discuss the possible biotechnological applications of Crotalaria.